2017
DOI: 10.1080/00207454.2017.1280793
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia as a prognosis predictor of length of stay and functional outcomes in patients with acute ischemic stroke

Abstract: Hyperglycemia is a prognosis predictor of LOS and functional outcomes of patients with acute ischemic stroke measured by discharge Barthel index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 17 publications
2
24
0
6
Order By: Relevance
“…Geographically, the mean prevalence of diabetes in stroke inpatients was highest in Southeast Asian (Singapore, India, Indonesia) and East Asian countries (China, Japan, Taiwan), which were 33.5 and 32.3%, respectively, and mostly in Taiwan. The mean prevalence in studies from North America and Europe was 27.5 and 26.4%, respectively.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Geographically, the mean prevalence of diabetes in stroke inpatients was highest in Southeast Asian (Singapore, India, Indonesia) and East Asian countries (China, Japan, Taiwan), which were 33.5 and 32.3%, respectively, and mostly in Taiwan. The mean prevalence in studies from North America and Europe was 27.5 and 26.4%, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Stress hyperglycemia has been associated with poorer functional outcomes and mortality, irrespective of diabetes status after an acute ischemic stroke. However, more studies have found that stress hyperglycemia has been associated with infarct volume growth, early neurological deterioration (increase of ≥4 points on National Institute of Health Stroke Scale), poorer functional outcome, higher mortality and longer hospital stay in people without a history of diabetes, including patients who underwent thrombolysis and mechanical thrombectomy. This association remained even after adjusting for stroke severity and stroke subtype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Type 2 diabetes mellitus (DM) is one of major risk factors of stroke and hyperglycemia at the time of acute ischemic stroke increases the risk of hemorrhagic transformation with iv-TPA treatment and it is associated with poor clinical outcomes, longer inhospital stay, increased cost, and mortality [1][2][3][4][5][6]. However, it hasn't been established how to manage hyperglycemia safely in an acute stroke stage, particularly in cases of high-dose insulin users.…”
Section: Introductionmentioning
confidence: 99%